Validity of Biology Practicum Guidebook based on Science Literature for High School Class XI Students - Siregar, Khairunnisyah Siregar; Restuati, Martina Restuati; Gultom, Tumiur Gultom (META: Journal of Science and Technological Education, 2022)
The importance of practicum in reaching learning goals, particularly in the subject of science, is crucial, given that practicum is an inherent component of teaching and learning activities. In order for students to comprehend things more thoroughly, practicum serves as a technique of concretizing previously abstract materials and equipment. The development of scientific literacy-based practicum guidebooks is expected to propel the significance of practicum. This study will examine how the degree of validity of biology practicum guidelines based on scientific literacy for eleventh-grade students. This research approach use the Borg and Gall (1989) model to conduct development research. The presentation ratings were 91.5% (very good), 86.48% (very good), and 89% (very good) based on the validation of material experts, scientific literacy experts, and media design experts, respectively. This biology practicum guidebook based on science literature for high school class XI students is therefore suitable for use, according to the results of validation by experts.